Cacao plant is one of the major commodity of plantation in South East Sulawesi, especially in Konawe regency. Practices of land management implemented by the local cacao farmers in many cases are not in accordance to soil and water conservation principles until caused of soil degradation. The research was aimed to investigate the alteration of soil physics properties on the local farmers cacao cropping land at different slope as related to canopy cover. The research was conducted in Amosilu V - Nurmi .; Oteng Haridjaja; Sitanala Arsyad; Sudirman Yahya (Forum Pasca Sarjana, 2009)
Cacao plant is one of the major commodity of plantation in South East Sulawesi, especially in Konawe regency.  Practices of land management implemented by the local cacao farmers in many cases are not in accordance to soil and water conservation principles until caused of soil degradation.  The research was aimed to investigate the alteration of soil physics properties on the local farmers cacao cropping land at different slope as related to canopy cover.  The research was conducted in Amosilu Village, Besulutu District, Konawe Regency, the Province of South East Sulawesi, from December 2006 to September 2007.  The experimental method with field study was applied in split plot design consisting of three factors, namely (i) slope consisting of two levels (10-15% and 40-45%) and (ii) age of the cacao plant consisting of two levels (5 to 7 months and 25 to 27 months) were used as main plots (P1 = 5 to 7 months and 10-15%; P2 = 25 to 27 months and 10-15%; P3 = 5 to 7 months and 40-45%; and P4 = 25 to 27 months and 40-45%), while (iii) vegetatif conservation treatment was used as sub plots consisting of three levels, i.e T1 = cacao with disc clearing, T2 = dry field rice and soybean rotation within cacao plant, T3 = T2 + Arachis pintoi as strip plant.  There was not interaction between both cacao plant and slope treatment with vegetative conservation treatment to soil physics properties, exception on aggregate stability index.  The result showed that vegetative conservation treatment (T1) that is cacao with disc clearing was best alternative because they implied the higher rate of total porosity (61,8%) and the lower rate of bulk density (1,013 g cm-3) as soon as the raising of aggregate stability index as well.   Key words: cacao, canopy cover, conservation, soil physics properties